The Implementation of Sociodrama to Reduce Bullying Behaviour of Islamic Junior High School Students - Irmayanti, Rima (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
The aim of this research is to reduce the bullying behaviour by implementing sociodrama method to second grade students in YPMI Islamic Junior High School Wanayasa - Purwakarta. The research method used in this research is quasi experimental; with pretest-posttest control group design. Purposive sampling is used to collect the sample and questionnaire is used to collect the data which has been statistically validated and accepted by Counselling Guidance Expert. The treatment is given to the experimental class in four session. The result of the pre-test score in experimental class has reduced from 47.13 to 41.29 in the post-test. Meanwhile, controlled class score has increased from 42.00 to 43.80. Based on the Sig. (2-tailed) experimental class is 0.000 < 0.05, so Ha is accepted, it means the sociodrama method could reduce the bullying behaviour in second grade students of YPMI Islamic Junior High School.